(untitled) (GYMNASIUM, 2017)
The study had an exploratory nature, aiming at preparing the moral-volitional implications in training athletes. This was done using the special survey method outlined in construction, questionnaires and their interpretation. The research aimed to highlight the importance of volitional and moral training for athletes. So we started from the consideration that, to practice a sport at a high level, athletes must, in addition to sports training and preparation needed moral will and aware of the need variables. From the research conducted, it was found that the battle with self and self-control are the drivers will educate the athlete and his morality. These issues were highlighted through the behavior of the respondents, finding that self, attitudes, behaviors are prevalent in fair play conduct sports competitions and training.